Prospective Scenarios for Female Entrepreneurship at the Base of the Pyramid - Santafé- Rojas, Akever Karina; Tuta- Ramírez, Laura Teresa (Universidad Francisco de Paula Santander, 2019)
In recent years, society has been transformed from the contribution of entrepreneurship, which has become a tool for socioeconomic development in the face of social inequality in the regions. In this sense, women permeate society with their participation from the entrepreneurial exercise, mitigating the inequality gap. Therefore, the purpose of the study is to propose prospective scenarios for female entrepreneurship at the base of the pyramid. From the methodological process, the research is typified in the interpretive position, under the qualitative approach with phenomenological orientation, applied to an expert and 3 key informants, which allowed the approach of the prospective structural analysis method, by articulating a matrix that relates all the constituent elements of the investigation. Therefore, it is inferred that the prospective study generates a collective reflection structure of imperative scenarios for the development of female entrepreneurship at the base of the pyramid in the study area, by identifying strategic guidelines that will improve the quality of life, the environment family and social of the population.